Estudo comparativo da eficiência de diferentes métodos de acompanhamento para painéis solares - Coelho, Wanderson Araújo (Universidade Federal Rural do Semi-Árido, 2018)
Invisioning the capacity of systems to generate and distrubute eletric power, despite of the needs to reduce enviroments impacts and the rising search for renewable sourches of energy, the photovoltaic technology for the capaciting cells of solar radiation has been more used nowadays. To make a comparative study on solar tracking the use of photovoltaic cells has shown more effience, analasing the viability on the usage and the current consumption of eletric power, the correct use of trackers is the main key to a solar tracking system. A comparative study on the efficience of different tracking methods or the accompaniment of solar panels were made. In order to make this monitoring four photovoltaic systems were used, the first one having trackers on two of the systems axles, the second one being tracked in only one axel, a third one with the system attached on the horizontal position, and the fourth one established with a 30 degree inclination. The prototype with two axels has shown better efficience. The potency developed by the panel which has solar trackers with moviment in two axels is approximately 25% larger when compared with the solar tracker with only one axle and at about 66% bigger in comparison to the other two established systems.
Monografia
Keywords: Rastreador solar; Protótipo; Eficiência; Painel fotovoltaico; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA